1995
DOI: 10.1246/cl.1995.561
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Absorption Characteristics of Crystalline LaNi5 Prepared by Mechanical Alloying

Abstract: Crystalline LaNi5 powder was synthesized by mechanical alloying of constituent metals preceding annealing at lower than a melting point of the alloy. The structure of the sample as mechanically alloyed was amorphous. After two-step heat treatments at 723 K in a stream of hydrogen and at 1273 K in helium, the crystalline sample was obtained. The hydrogen absorption characteristics of the crystalline sample were in fair agreement with those of the alloy prepared by a conventional melting technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…On the other hand, mechanical alloying seems to be a suitable procedure for the synthesis of nanocrystalline AB 5 alloys [148][149][150]. When milling is performed under an inert atmosphere, hydrogen can be readily absorbed if the milled powder is not exposed to the air [151].…”
Section: Abmentioning
confidence: 99%
“…On the other hand, mechanical alloying seems to be a suitable procedure for the synthesis of nanocrystalline AB 5 alloys [148][149][150]. When milling is performed under an inert atmosphere, hydrogen can be readily absorbed if the milled powder is not exposed to the air [151].…”
Section: Abmentioning
confidence: 99%
“…At the same time, the product can be produced easily by ball milling. [51,52] A material synthesized in such a manner exhibits improved hydrogenation and dehydrogenation kinetics, [53] see Figure 8. It was also shown that a nanocomposite produced by ball milling of the immiscible metals Fe and Mg exhibits better hydrogenation kinetics and reversible capacities for hydrogen than the same material produced by sintering.…”
Section: Nanocompositesmentioning
confidence: 99%
“…The mechanochemical method allows to change thermal stability of a hydride phase, to decrease/increase temperature of its decomposition or a phase transition, to expand significantly a region of the ␣-solid solution or to constrict a two-phase region, to change equilibrium pressure, etc. [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%